Design of Earthquake Warning Alarm Using Accelerometer Sensor Based on Internet of Things - Gunoro; Suprapto; Juli Iriani; Bakti Viyata Sundawa; Abdullah; Cholish (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Earthquake is natural event due to release of energy suddenly from within that creates seismic waves. The vibrations are usually caused by movement of earth's plates. It cannot be predicted when they are coming. Therefore, need to build an early warning system. It is for anticipation of save the community when an earthquake occurs. It provides solutions to minimize the impact of earthquake events. This system uses accelerometer sensor and arduino nano as a main controller and it is accompanied by Blynk application. This works for sent notification via smartphone. This tool has been successfully designed with manual testing to be able to see the sensitivity of earthquake sensor made. Accelerometer sensor works is using Tilt Method. Accelerometer sensor will tilt on surface as parable of earthquake. Accelerometer sensor will send vibration signal when earthquake occurs. Signal processing is done by Arduino nano as the main controller in system. If the signal is received by sensor then value of earthquake will be displayed on LCD screen. Status of earthquake was separated into 4 levels such as standby, alert, dangerous, dangerous and dangerous. After earthquake value appears on the LCD screen and the status is known then buzzer will sound. It indicates that the earthquake warning alarm is properly functioning. Next, NodeMCU also sends information to Blynk application, which is used as a notification and monitoring of earthquake conditions. Buzzer will sound as a warning alarm to notify peoples to save themselves. This sensor has three output coordinate points, namely X, Y, Z, which have analog values ​​on Arduino Nano. This analog value can be converted into Richter Scale. Based on experimental results, an analog value is 100 – 400.